ANALISIS FRAMING PADA PEMBERITAAN VAKSINASI DI KOMPAS.COM DAN CAKAPLAH.COM - Santi "; Tutut Ismi Wahidar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Covid-19 vaccination is the administration of vaccines in order to actively generate or increase a person's immunity against diseases caused by the Covid-19 virus. Online media Kompas.com and Cakaplah.com are the national media and local media that mostly report on vaccinations from November to December 2021. There are 7 news stories about vaccinations on Kompas.com and 25 news stories on Cakaplah.com online media. Researchers are interested in discussing framing on vaccination news in the online media Kompas.com and Cakaplah.com in the period November-December 2021. This study uses a qualitative descriptive research method using Robert N's model of framing analysis with agenda setting theory. Robert N. Entman's framing analysis highlights certain aspects with certain realities, which will reveal how the news framing carried out by the online media Kompas.com and Cakaplah.com for reporting vaccination activities in Pekanbaru. The results of this study indicate that the differences in news writing are motivated by differences in the perspectives of each media. Compiled based on 4 elements from Entman, namely Define Problems: the researcher found that Kompas.com provides a consistent perspective on vaccination achievements in Riau. Meanwhile, at Cakaplah.com, the results were found to raise a lot of news about vaccinations in detail. Diagnose Causes (estimating the problem): Kompas.com in estimating the problem only conveys some resistance to the community. Meanwhile, Cakaplah.com tends to estimate the problem in more detail regarding the vaccination target to be achieved. Make Moral Judgment: Kompas.com and Cakaplah.com present news with accurate data from trusted institutions or sources. Treatment Recommendation (emphasizing completion): In presenting the news, Kompas.com only provides information to the public, while the news on Cakaplah.com is more directed to the collaboration between the Government and the community who will carry out vaccinations. Keywords: Framing Analysis, Vaccionations News, Cakaplah.com and Kompas.com